Nitrogen Removal from Landfill Leachate by Microalgae - Sérgio F. L. Pereira (2016)
Landfill leachates result from the degradation of solid residues in sanitary landfills, thus presenting a high variability in terms of composition. Normally, these effluents are characterized by high ammoniacal-nitrogen (N-NH4+) concentrations, high chemical oxygen demands and low phosphorus concentrations. The development of effective treatment strategies becomes difficult, posing a serious problem to the environment. Phycoremediation appears to be a suitable alternative for the treatment of landfill leachates. In this study, the potential of Chlorella vulgaris for biomass production and nutrients (mainly nitrogen and phosphorus) removal from different compositions of a landfill leachate was evaluated. Since microalgae also require phosphorus for their growth, different loads of this nutrient were evaluated, giving the following N:P ratios:12:1, 23:1 and 35:1. The results have shown that C. vulgaris was able to grow in the different leachate compositions assessed. However, microalgal growth was higher in the cultures presenting the lowest N-NH4+ concentration. In terms of nutrients uptake, an effective removal of N-NH4+ and phosphorus was observed in all the experiments, especially in those supplied with phosphorus. Nevertheless, N-NO3- removal was considered almost negligible. These promising results constitute important findings in the development of a bioremediation technology for the treatment of landfill leachates.